Analisis Identifikasi Potensi Wisata Di Desa Medalsari Kecamatan Pangkalan Kabupaten Karawang - Jenal Abidin; Lala Siti Sahara; Rahmat Darmawan (STIE Pariwisata API Yogyakarta, 2023)
Medalsari Village is a village located in Pangkalan District, Karawang Regency which has the potential to become a community-based tourist destination with the concept of a tourism village. The aim of this research is to identify and analyze the tourism potential of Medalsari Village and how its development is directed. This study used a qualitative approach with an analytical descriptive method. Data collection using interviews and field observations. The data collected was then analyzed qualitatively. The results of the study illustrate that Medalsari Village has the potential for natural tourism, cultural tourism and educational tourism, based on the SWOT analysis there are potentials, opportunities and challenges that must be carried out in developing Medalsari Village as a Tourism Village.